Risk Factors of Dental Caries in Primary School Children: A Systematic Literature Review - Zita Aprillia; Mohammad Zen Rahfiludin; Henry Setyawan Susanto; Syamsulhuda Budi Mustofa (GLOBAL HEALTH SCIENCE GROUP, 2026)
Dental caries is a chronic infectious disease with a high prevalence in elementary school-aged children (6–12 years) globally. This condition is influenced by the complex interaction of various determinants of health. This study aims to identify and synthesize the dominant risk factors for the occurrence of dental caries in elementary school-age children based on the latest scientific evidence. Systematic review was conducted following the PRISMA 2020 guidelines. A comprehensive literature search was conducted on the Scopus and PubMed databases for English-language articles published in the time range November 2022 to November 2025. Inclusion criteria include cross-sectional, cohort, case-control studies that analyze caries risk factors in elementary school-aged children of 6–12 years. Of the 1,422 articles identified from three databases, 11 studies met the eligibility criteria and were included in the final analysis. The main risk factors are categorized into behavioral and lifestyle aspects, socio-demographic, and socioeconomic. The findings suggest that high-sugar diet behaviors (sugary snacks and soft drinks) and poor oral hygiene (rarely brushing and not using dental floss) were the dominant factors. Socio-demographically, low parental education levels, low socioeconomic status, and male gender have a significant association with an increased risk of caries. In addition, the presence of dental plaque and tooth morphology (deep gaps) are important biological determinants. Dental caries in elementary school children is multifactorial, but lifestyle factors related to diet and oral hygiene, as well as family socioeconomic background are the main determinants. Effective prevention strategies require a holistic approach that focuses on modifying children's behavior and improving parental education.